QUESTIONING ALIENATION OF HUMANITIES DISCIPLINE IN ENGLISH EDUCATION CURRICULUM - Setiawan, Rahmat; Andanty, Ferra Dian (University of Muhammadiyah Malang, 2024)
The English language education curriculum tends to focus on technical language issues (skills) and educational aspects. In fact, language proficiency is acquired through practice, training, and habit. Educators must have cognitive, psychological, and sociological understanding. This is the problem: English language learning tends not to involve the humanities in its curriculum. This research aims to explore the factors that make the English Education curriculum less likely to include humanities disciplines while it has crucial impact to the quality of English teaching and learning. In methodology, the type of research is qualitative. The approach in this research is case study. The data collection technique in this research is Focus Group Discussion (FGD). The type of FGD used in data collection is Single Focus Group which supports an explorative space to support the provision of data in the analysis. There are three parts to conducting FGDs: pre-activity, activity, and post-activity. The research employs the thematic analysis technique. There are three main results can be drawn implicitly by the researcher from the perspective of the English Education lecturers: Theoretical-Based Orientation, Skillset Target, and Positivistic Ideology. Firstly, the English Education curriculum processes English language learning through theories. Secondly, the English Education curriculum focuses on the English language skillset. Thirdly, the English Education curriculum aims to produce English teachers who will teach English focusing on the learning process and the learners’ internal problems in the classroom, not the learners’ external problems.